Stability and success of regional fisheries management organizations - Pedro Pintassilgo; Michael Finus; Marko Lindroos; Gordon Munro (Fondazione Eni Enrico Mattei (FEEM), 2008)
According to international law, straddling fish stocks should preferably be managed cooperatively through regional fisheries management organizations (RFMOs). This paper analyzes the stability and success of these organizations through a game in partition function form based on the classical Gordon-Schaefer bioeconomic model. A comprehensive analysis of the economic and biological fundamentals that influence the success of coalition formation is provided. The results show that the larger the number of fishing states that compete for the fish stock the higher would be the relative gains from full cooperation, but the lower is the likelihood of large RFMOs being stable. It is also shown that the success of coalition formation is positively correlated with the degree of production cost asymmetry among fishing states and negatively with the overall level of efficiency.
Keywords: C72; Q22; 330; Straddling Fish Stock; Regional Fisheries Management Organizations; Unregulated Fishing; Bioeconomic Model; Coalition Formation Model; Free-Riding